TEACHING READING COMPREHENSION ON ANALYTICAL EXPOSITION TEXT BY USING MULTIPASS STRATEGY - Veneranda, Maria Gina; Marbun, Rismaya; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Email : mariaginaveneranda@gmail.com Abstract : Â The purpose of this research is to investigate whether or not multipass strategy increase studentsâ€™ achievement in reading comprehension on analytical exposition text. The method which was used in this research was pre-experimental study. The population of this research was all of eleventh grade students of SMA Negeri 1 Sungai Raya in academic year 2013/2014 and the sample was taken from class XI IPA 3 which consists of 36 students. The data had been collected by using measurements techniques. The tool of the data collecting was multiple choice tests. The data were calculated and the result showed that the mean score of studentsâ€™ pretest of experimental group was 59,19 while the posttest was 80,72. The different score between pretest and posttest was 21,53.Â Moreover, the result of Effect Size was 1.06 (categorized as â€œstrong effectâ€ refers to the criteria of effect size table). The calculation of the t-test shows that the t-ratio was higher than the t-value (9,08> 2,03 at Î± 5%). Therefore the null hypothesis was rejected and the alternative hypothesis was accepted. In conclusion, there was a significance difference of the studentsâ€™ mean score in reading comprehension on analytical exposition text between pre-test and post-test after the treatment. Key Words : Reading Comprehension, Analytical Exposition Text, Multipass Â Â Â Â Â Â Â Â Â Â Â Â Strategy Abstrak : Penelitian ini bertujuan untuk menyelidikiÂ efektifitas penerapan multipass strategi dalam meningkatkan prestasi belajar siswa pada pemahaman membaca teks eksposisi analitis. Metode yang digunakan dalam penelitian ini adalah penelitian pre-eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas XI di SMA Negeri 1 Sungai Raya pada tahun akademik 2013/2014 dan sampel diambil dari kelas XI IPA 3 yang terdiri dari 36 siswa. Data dikumpulkan dengan menggunakan teknik pengukuran. Alat pengumpulan data berupa tes yang berbentuk pilihan ganda. Berdasarkan hasil perhitungan data didapati bahwa nilai rata-rata pre-test siswa adalah 59,19 dan nilai rata-rata post-test adalah 80,72. Selisih nilai antara pre-test dan post-test adalah 21,53. Selain itu, hasil perhitungan nilai efektifitas adalah 1,06 ( termasuk kategori â€œkuatâ€ berdasarkan kriteria dalam tabel ukuran efektifitas). Perhitungan t-test menunjukkan bahwa t-hitung lebih besar daripada t-tabel (9,08> 2,03 dengan Î± 5%). Oleh sebab itu maka hipotesis null ditolak dan hipotesis alternatif diterima. Sebagai kesimpulan, ada perbedaan yang cukup signifikan antara pre-test dan post-test pada nilai rata-rata siswa dalam pemahaman membaca teks eksposisi analitis setelah diberikan perlakuan. Kata kunci : Pemahaman membaca, teks eksposisi analitis, multipass strategi